P85 Successful implementation of case finding for hepatitis C in people detained in police custody. (19th June 2022) - McCullough, Francesca; Allsop, Caroline; Miller, Carolyn; Askar, Sumar; McQue, Kate; Jelley, Ryan; McTeer, Gary; Jones, Kerry; Gooding, Sarah; McPherson, Stuart
Abstract : Introduction: As part of the national Hepatitis C (HCV) elimination strategy, NHS England aims to eliminate HCV by 2025. As part of this programme, identifying undiagnosed cases through HCV testing is critical. Unfortunately, the global COVID 19 pandemic led to a reduction in HCV testing in England, potentially slowing progress towards elimination. To mitigate the impact of this, innovative ways of increasing HCV testing are required. Individuals detained in police custody have higher rates of injecting drug use than the general population and may therefore be at risk of HCV transmission. Police custody suites may therefore provide an opportunity to offer HCV testing to 'at risk' individuals. In collaboration with local police custody healthcare staff, we developed a pilot of HCV testing for individuals in police custody. Here we describe the outcomes of this pilot Methods: Since 01/07/2021, all individuals presenting to Northumbria police custody suites who were reviewed by a healthcare professional were offered Dried Blood Spot test (DBS) for HCV Antibody/RNA, HIV and HBsAg. Individuals were excluded if they were <16 years of age or alleged perpetrators of sexual violence. The Newcastle HCV team were responsible for informing people of their results and establishing those with a positive HCV result on a treatment pathway. Results: Of the 3116 people in police custody identified as eligible to be offered BBV testing (See figure 1 ), 193 accepted (6%). A total of 19 were HCV Ab positive (10% of total individuals tested) and of these 12 were HCV RNA detected (63.0% of HCV Ab positive and 6% of total individuals tested). No cases of HIV or hepatitis B were identified. 137 (71.0%) individuals were negative for all BBV's. Unfortunately, 37 (19%) samples could not be processed by the lab due to insufficient samples (19.0%). This was identified as a training issue and addressed by senior custody suite staff. of the 12 cases of active HCV identified, 5 have commenced HCV antiviral treatment, 6 are awaiting treatment and 1 person is awaiting retesting as the result was 'weak positive'. of the 7 individuals who were HCV Antibody positive but RNA negative, 3 had self-cleared, 3 were known to have received antiviral treatment and achieved a sustained virological response and 1 patient was currently on treatment. Conclusions: The pilot demonstrated that HCV screening can successfully be implemented into the police custody suites, leading to a diagnosis of active HCV in 6%. Wider implementation of this strategy could help progress towards HCV elimination.